H. Pylori Gastritis and Gastric Carcinoma: Uncovering Histological Links and Risk Factors - Wajid Iqbal, Rashid Karim, Ahsan Ali Memon, Kapeel Raja, Tanweer Ahmed Shaikh, Syed Usama Shayan Zaidi (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Aim was to determine the risk of gastric carcinoma among patients of Helicobacter pylori gastritics and its risk factors. Study Design: Retrospective study Place and Duration: Department of gastroenterology, DHQ Teaching Hospital and Ghazi Khan Medical College DG Khan, Punjab in the duration from November, 2022 to April, 2023. Methods: Total 131 patients who had gastric carcinoma were included. Stored serum samples collected, were tested for IgG antibodies to H. pylori by enzyme-linked immunosorbent assay. Data on cigarette use, blood group, ulcer disease, and gastric surgery were obtained from questionnaires administered at enrollment. Tissue sections and pathology reports were reviewed to confirm the histologic results. SPSS 23.0 was used to analyze data. Results: In our study, male patients were higher in numbers 86 (65.6%) as compared to females 45 (34.4%). The patients mean age was 51.17±6.20 years and had mean BMI 24.16 ±7.46 kg/m2. 73 (55.7%) patients had smoking history. 97 (74.04%) patients had gastric ulcer. Average time from serum collection to stomach gastric carcinoma was 12.7±3.26 years. Among all, 74 (56.5%) patients had adenocarcinoma, gastroesophageal junction was found in 20 (15.3) cases, gastric lymphoma in 11 (8.4%) cases and 26 (19.4%) cases had undetermined or other cancers. We found that 83 (63.4%) patients had history of H.pylori infection. There was a significant negative association between a history of peptic ulcer disease and eventual gastric carcinoma (P = 0.003) and an independent association between a history of gastric surgery and the development of cancer (p = 0.004). Conclusion: The results of this research led us to the conclusion that an infection with H. pylori is linked to an elevated risk of gastric adenocarcinoma and may play a role as a cofactor in the process that leads to the development of this malignant condition. Keywords: H.pylori infection, Gastric Carcinoma, Risk Factors